Analisis Pengaruh Faktor Fundamental, Teknikal dan Makro Ekonomi Terhadap Harga Saham Pada Perusahaan Subsektor Kimia yang Terdaftar di Indeks Saham Syariah - Nabila Nurliandini; Endang Hatma Juniwati; Setiawan Setiawan (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
This research was aims to analyze the influence of fundamental factors including Current Ratio (liquidity ratio), Return on Equity (profitability ratio), Debt to Equity Ratio (solvability ratio), technical which includes trading volume and macro economy including inflation ,and exchange rates on stock prices in chemical sub-sector companies listed on the Sharia Stock Index (ISSI) for the period 2015 - 2019. The sample consisted of 17 companies. The type of data used is quantitative data sourced from the official websites of the Indonesia Stock Exchange (IDX), Bank Indonesia (BI) and the Central Statistics Agency (BPS). The sampling technique in this study used a purposive sampling technique. The data analysis technique used is panel data regression analysis. The results of this study show simultaneously the variables CR, ROE, DER, Trading Volume, Inflation, and Exchange Rates. Meanwhile partially, ROE has a positive and significant effect on the stock prices of chemical sub-sector companies listed on the Sharia Stock Index (ISSI). Meanwhile, other variables, CR, DER, Trading Volume, Inflation, and Exchange Rates partially have an effect but are not significant on the stock prices of companies listed on the Index. Sharia Shares (ISSI).